The pathogenic role of intestinal flora metabolites in diabetic nephropathy - Tian, En; Wang, Feng; Zhao, Lei; Sun, Yan; Yang, Jurong (Frontiers in Physiology, 2023)
With the increasing incidence of diabetes, diabetic kidney disease has become a major cause of chronic kidney disease. The role of the gut microbiota in diabetes and its related complications have been extensively investigated; the modulatory effect of the gut microbiota on the host depends on several gut microbial metabolites, particularly short-chain fatty acids, secondary bile acids, and trimethylamine N-oxide. In this review, we focused on the evidence related to the pathogenic role of each of the gut microbial metabolites in diabetic nephropathy. The main novel therapies targeting the gut microbiota include probiotics, dietary prebiotics, synbiotic supplements, and faecal microbiota transplants, although there is no standard treatment principle. Further research is therefore needed to elucidate the link between gut microbes and diabetic nephropathy, and more therapeutic targets should be explored to treat diabetic nephropathy with dysbiosis of the gut microbes.